THE CONCENTRATION OF THE CHEMICAL COMPOUNDS AND THE COLOR OF BERRY TO THE VARIETIES OF THE INTERSPECIFIC HYBRIDS TO THE VINES (VITIS VINIFERA L. X MUSCADINIA ROTUNDIFOLIA MICHX.). - Eugeniu ALEXANDROV (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
The color of the berry vine is a very stable morphological character and some varieties can only be determined based on this indicator. The diversity of berry vine color is due to the biochemical characteristics of the juice berry. The concentration of resveratrol from the juice of the berry of interspecific hybrids of vineyards (Vitis vinifera L. x Muscadinia rotundifolia Michx.) is consistent with the color of the berry. So yellowish-green berry contain the 6.68 mg/l, berry rosy color - 9.3 mg/l and blue-violet berry - 14 mg/l of resveratrol. As a result of studies carried out it was found that hybrids from third (BC2) generation is characteristic of a higher concentration of diglucozid-3,5-malvidol and methyl anthranilate than hybrids from fourth generation (BC3). So it once the removal from the parental forms, the concentration of these chemical compounds in the juice of berry the interspecific hybrids of the vineyards (Vitis vinifera L. x Muscadinia rotundifolia Michx.) is decreasing.